An L-RNA Aptamer That Binds and Inhibits Ribonuclease - Olea, Charles (Chem Biol, 2015)
L-RNA aptamers were developed that bind to barnase ribonuclease and thereby inhibit the function of the enzyme. These aptamers were obtained by first carrying out in vitro selection of D-RNAs that bind to the full-length synthetic D-enantiomer of barnase, then reversing the mirror and preparing L-RNAs of identical sequence that similarly bind to natural L-barnase. The resulting L-aptamers bind L-barnase with an affinity of ~100 nM and function as competitive inhibitors of enzyme cleavage of D-RNA substrates. L-RNA aptamers are resistant to degradation by ribonucleases, thus enabling them to function in biological samples, most notably for applications in molecular diagnostics and therapeutics. In addition to the irony of using RNA to inhibit ribonuclease, L-RNA aptamers such as those described here could be used to measure the concentration or to inhibit the function of ribonuclease in the laboratory or in biological systems.